Perception of Rabies among Residents of Selected Local Government Areas of Oyo State, Nigeria (2016)
"Rabies, a fatal neurotropic disease of man and animals is usually a neglected disease in many parts of the world probably because of the erroneous belief that it affects animals predominantly. This study was designed to investigate the knowledge and attitude of people in selected communities of Oyo State, Nigeria with the aim of assessing the possible risk of getting infected with the virus. A total of 323 participants were randomly selected from 10 local government areas of Oyo State, Nigeria and interviewed using a pre-tested structured questionnaire. The results were analysed using descriptive statistics and Pearson’s chi square method. Information obtained included the demographic characteristics of the participants, their interaction with dogs, knowledge about rabies and its fatality, its mode of transmission and prevention as well as the perception of and attitude of people towards rabies. Of the 323 participants, 180(55.8%) were male while 143(44.3%) were female, 115(47.7%) were Christians, 123(51%) were muslims and 3(1.2%) were traditional religion adherents. Furthermore, 263(81.4%) had different levels of education 60(18.6 %) were illiterate, 119(36.8%) used to own dog while only 54(16.4%) presently kept dogs for reasons which included hunting 16(30.1%), security 28(52.8%), breeding {3(5.66%)} and as companionship 6(11.3%). Greater number (80%) lived in the rural areas while 62(19.6%) were urban dwellers. Out of the 323 participants, 256 (79.5%) knew about rabies, of these, 46(18%) heard about the disease from awareness campaigns, 11(4.3%) heard from human and veterinary hospitals 58(22.7%) heard from interpersonal interactions while 123(48.1%) knew by personal experiences. From the people that claimed knowledge, 231(90.2%) knew that rabies was a fatal disease, 96(37.5%) knew about rabies in other animal species aside dogs, 110(43%) knew about rabies transmission by dog or cat bite, 24(9.4%) knew that rabies can be transmitted by wild animals. Also, 130(50.8%) claimed knowledge of rabies prevention in animals but 88(34.4%) only knew about antirabies vaccination.in animals. Similarly, 128(50%) claimed knowledge of rabies prevention in man and of these, 38(14.8%) recommended prophylactic and post exposure antirabies vaccination, 42(16%) hospital visits, 20(7.8%) dog elimination and staying away from dogs, while 12(4.7%) recommended religious means, and use of herbs. When asked about first aid treatment, 99(38.7%) suggested wound washing with soap and antiseptic, 171(66.8%) recommended hospital visit while 40(15.6%) suggested a visit to the herbalist for the antidote. Pearson’s chi square showed significant difference (P<0.05) in the knowledge of the respondents and marital status. Poor knowledge of some aspects of rabies and negative attitude of dog owners towards rabies may portend grave public health consequences.